2016
DOI: 10.1186/s10194-016-0627-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of paediatric headache – sex-specific analyses and predictors

Abstract: BackgroundHeadache is the most common pain disorder in children and adolescents and is associated with diverse dysfunctions and psychological symptoms. Several studies evidenced sex-specific differences in headache frequency. Until now no study exists that examined sex-specific patterns of change in paediatric headache across time and included pain-related somatic and (socio-)psychological predictors.MethodLatent Class Growth Analysis (LCGA) was used in order to identify different trajectory classes of headach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 69 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…Our results support recent findings that special consideration should be given to female adolescents [ 33 , 34 ]. Other studies have revealed a higher incidence of headache as well as a higher burden, clinical heterogeneity and higher psychological comorbidity such as depression and anxiety in girls as compared to boys [ 6 , 13 , 33 , 35 ]. However, this sex discrepancy seems to become relevant only from adolescence on [ 4 , 6 , 10 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support recent findings that special consideration should be given to female adolescents [ 33 , 34 ]. Other studies have revealed a higher incidence of headache as well as a higher burden, clinical heterogeneity and higher psychological comorbidity such as depression and anxiety in girls as compared to boys [ 6 , 13 , 33 , 35 ]. However, this sex discrepancy seems to become relevant only from adolescence on [ 4 , 6 , 10 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a familiar predisposition was reported in 50.3% of students in Group 1, but this rate was significantly higher in females (54.3% vs 45.4%). Isense et al suggest that in recognizing parental headache as a risk factor, not only genetic predisposition should be considered, but also the influence of dysfunctional pain-related modelling mechanisms: in this perspective, parental perception of and coping with headache may very soon influence the child’s cognitive, emotional and behavioral coping with pain, influencing intensity, frequency and pain-related disability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in a similar, clinic-drawn sample of paediatric chronic have also observed increased impairment (including pain severity, depression and anxiety) with increasing age (54). Interestingly, psychiatric co-morbidities in late adolescence have been associated with a worsening or endurance of headache at eight-year follow-up (55) and in girls, but not boys, anxiety/depression was found to be a significant predictor of headaches over four years (56). Under this view it is possible that the association between psychiatric co-morbidities and the burden caused by migraine may perpetuate both conditions over time, particularly for girls (57).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, our research group used Latent Class Growth Analysis (LCGA) (30,31) to identify sex-specific headache trajectories of 3227 children and adolescents (9–14 years old at first assessment) from a population-based sample who completed four annual assessments (32). In order to find the best-fitting model, statistical fit indices (e.g.…”
Section: Introductionmentioning
confidence: 99%